A semantic analysis of conjunctions in the translation of Badai Semalam into English / Nur Farhana Nasri - Nasri, Nur Farhana (2014)
The purpose of this study is to analyze the semantic analysis of conjunctions in the translation of a Malay-English novel. This study focuses on looking at cohesion ties specifically conjunctions used in the selected Malay literary text, Badai Semalam and its English translated version, Storms of Yesterday. The objectives of this study are (i) to identify the types of conjunctions used in sentences in translating the Malay novel, Badai Semalam into the English novel, Storms of Yesterday (ii) to find out the similarities and differences of semantic features of the Malay conjunctions into the English translation (iii) to determine the types of shifts in the level of explicitness and shifts in text meaning that might occur in the English translation. The study will employ Halliday and Hasan’s Taxonomy of Cohesion (1976) which emphasizes on conjunctions of four semantic areas (additive, adversative, causal and temporal) with the conjunctions in Malay language. In addition, Componential Analysis by Katz and Fodor (1963) will also be used to determine the semantic features of conjunctions whether the conjunctions used in Malay and English are similar or different. Blum Kulka’s shifts of Cohesion (1986) will be used to examine the types of shifts in the level of explicitness and text meaning that might occur. A pilot study was done earlier to require a comprehensive result before it is written completely. The discussions on the findings are presented from the excerpts of both novels and analyzed thoroughly. The findings reveal that some Malay and English conjunctions are related, overlapping and different. Interestingly, the results of the study also found that some Malay conjunctions are considered as prepositions and pronouns in English, thus indicates the frequent occurrences of explicit shifts.